2014
DOI: 10.1136/bmj.g3496
|View full text |Cite
|
Sign up to set email alerts
|

Impact of community based, specialist palliative care teams on hospitalisations and emergency department visits late in life and hospital deaths: a pooled analysis

Abstract: Objective To determine the pooled effect of exposure to one of 11 specialist palliative care teams providing services in patients' homes.Design Pooled analysis of a retrospective cohort study.Setting Ontario, Canada.Participants 3109 patients who received care from specialist palliative care teams in 2009-11 (exposed) matched by propensity score to 3109 patients who received usual care (unexposed). InterventionThe palliative care teams studied served different geographies and varied in team composition and siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
183
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(191 citation statements)
references
References 32 publications
7
183
0
1
Order By: Relevance
“…5 A recent study showed that different community-based team models in Ontario reduced hospital admissions and emergency department visits, provided certain key elements were present. 17 About 40% of the GP/FPs in our study did not use a single palliative care fee code. If the intention is to increase the capacity of primary palliative care, this may represent a target group or metric.…”
Section: Discussionmentioning
confidence: 81%
“…5 A recent study showed that different community-based team models in Ontario reduced hospital admissions and emergency department visits, provided certain key elements were present. 17 About 40% of the GP/FPs in our study did not use a single palliative care fee code. If the intention is to increase the capacity of primary palliative care, this may represent a target group or metric.…”
Section: Discussionmentioning
confidence: 81%
“…39 Palliative care consultations for patients with advanced cancer have also been shown to reduce the quantity and intensity of life-prolonging care received toward the EOL. [40][41][42][43][44] Conversely, the lack of palliative care team consultation has been shown to be a predisposing factor for futile life-sustaining treatments at EOL. 45 An observational study suggested that inpatient palliative care led to fewer or no transitions in care settings at EOL.…”
Section: Eol Care In Oncologymentioning
confidence: 99%
“…These services have been associated with a reduced need for EOL emergency department visits, reduced length and frequency of hospitalization, and fewer intensive care unit (ICU) admissions and in-hospital deaths. [40][41][42][43][44] Palliative care has been shown to reduce symptom burden, improve QOL, and increase the odds of dying at home. Similarly, a 2013 Cochrane Database systematic review that analyzed home palliative care in patients with advanced illness demonstrated a reliable reduction of symptom burden and an increased likelihood of dying at home without a negative impact on caregiver grief.…”
Section: Eol Care In Oncologymentioning
confidence: 99%
“…Os autores enfatizam a importância do atendimento domiciliar a estes pacientes visando a redução utilização de cuidados intensivos e óbitos hospitalares no final da vida (15).…”
Section: Discussão E Conclusãounclassified